Personal values, norms and sustainable consumption behaviours of beverage consumers in Central Uganda (International Journal of Applied Research in Management and Economics, 2023)
This study investigated the relationship between personal values, norms, and sustainable consumption behaviours of beverage consumers in central Uganda. The study employed a correlational design where 400 beverage consumers aged 18 and older provided the data in a survey. The data were analysed using structural equation modelling in the SPSS AMOS extension Version 23. The study results show that personal values and norms were critical determinants in beverage consumers’ engagement in sustainable behaviours like recycling, reusing, and proper disposal of waste from plastic bottles. Notably, consumers with biospheric values were more predisposed to engaging in such behaviours. Both personal and social norms positively influence sustainable consumption behaviours. The mediation effects of both norms were also confirmed in this research. Therefore, this study offers valuable insights to policy-making bodies and beverage companies in Uganda regarding the factors that drive sustainable consumption behaviours among beverage consumers. These findings can be used to develop effective environmental policies and marketing campaigns.